Southeast Europe: Regional Cooperation with Multiple Equilibria - Vladimir Gligorov (The Vienna Institute for International Economic Studies (wiiw), 2004)
It is argued in this paper that the lack of regional cooperation can be remedied by the speed up of the process of EU integration. That is reinforced by the considerations based on the theory of optimal currency areas. Though the current Stabilisation and Association process (SAP) may produce the same results though that process is riskier and requires more time.
Keywords: 330